The Influence of Expertise in Simultaneous Interpreting on Non-Verbal Executive Processes - Yudes, Carolina; Macizo, Pedro; Bajo, Teresa (Frontiers in Psychology, 2011)
This study aimed to explore non-verbal executive processes in simultaneous interpreters. Simultaneous interpreters, bilinguals without any training in simultaneous interpreting and control monolinguals performed the Wisconsin Card Sorting Task (WCST, Experiment 1) and the Simon task (Experiment 2). Performance on WCST was thought to index cognitive flexibility while Simon task performance was considered an index of inhibitory processes. Simultaneous interpreters outperformed bilinguals and monolinguals on the WCST by showing reduced number of attempts to infer the rule, few errors and few previous-category perseverations. However, simultaneous interpreters presented Simon effects similar to those found in bilinguals and monolinguals. Together, these results suggest that experience in interpreting is associated with changes in control processes required to perform interpreting tasks.